Proses Collaborative Governance dalam program Puspaga Balai RW di Kota Surabaya - Prakosa, Sakti Sigap; Bagus Nuari Harmawan (VISA: Journal of Vision and Ideas, 2024)
Puspaga, an abbreviation for Family Planning and Family Welfare Service Center, is a counseling service program that involves various community groups. This program integrates the concept of collaborative governance at the RW hall level, involving residents, community leaders, local government and related institutions. This collaboration aims to increase the effectiveness and sustainability of the Puspaga program amidst the changing paradigm of active community participation in development. RW Hall, as a center for social and cultural activities, is key in creating an environment that supports and understands community needs. Collaboration between RW halls, local government and other institutions is expected to create a holistic and sustainable service model.